Dual Network Sponge for Compressible Lithium‐Ion Batteries. Issue 26 (26th May 2021) - Wang, Zhipeng; Wang, Yunsong; Chen, Yijun; Wu, Huaisheng; Wu, Yizeng; Zhao, Xuewei; Han, Ray P. S.; Cao, Anyuan
Abstract: Compressible energy devices have received increasing attention with the rapid development of flexible electronics and wearable devices due to their size adaptability and functional stability. However, it is hard to simultaneously achieve satisfactory energy density and mechanical stability for electrodes. Here an open‐porous dual network sponge (DNS) with two networks of highly conductive carbon nanotubes and Li + ‐intercalating TiO2 ‐B nanowires is synthesized and employed as compressible lithium ion battery electrodes. All 1D components inside the DNS mutually penetrate with each other to form two physically distinct but functionally coupling networks, endowing DNS excellent compressibility and stability. A prototype compressible lithium‐ion battery (C‐LIB) is also demonstrated, in which the DNS exhibits a specific capacity of >238 mAh g −1 under static 50% strain, and further in situ measurements show that under 1000 times of cyclic strains, DNS can charge and discharge normally maintaining a high capacity of 240 mAh g −1 and exhibits robustness to fast strain rates up to 500% min −1 . The dual network structure can be extended to design high‐performance compliant electrodes that are promising to serve in future compressible and deformable electronics and energy systems. Abstract : Here, an open‐porous dual network sponge (DNS) with two networks of highly conductive carbon nanotubes and Li + ‐intercalating TiO2 ‐B nanowires is synthesized. With good compressibility and structural stability, it is used to fabricate compressible lithium‐ion batteries (C‐LIBs), which exhibit stable electrochemical performance under quantitative evaluation coupling mechanical strain and electrochemical characterization.